Influence Ceramic Powder SiC Moisture during Green Machining - Orlovsky, Imrich; Hatala, Michal; Duplak, Jan (Manufacturing Technology Journal, 2013)
This article describes the principle of Green Machining technologies and experimental tracking of moisture of ceramic granulate during the drying process. Green machining involves the machining of metal or ceramic bodies in the "green" state prior to sintering. Typically these bodies are comprised of ceramic or metal powder held together by an organic binder. In this state they are far easier to machine than monolithic blocks of the corresponding metal and ceramic. One of the materials that can be used in the green machining is silicon carbide. This material is produced in the process of spraying the emulsion in drying kiln. This process is very important considering the quality of ceramic powder with respect to its further use. One of the most important parameters to be monitored during the spraying is the moisture of the ceramic powder (granulate). [8][2]
Keywords: spraying; moisture; ceramic powder; green machining